2017
DOI: 10.1186/s40557-017-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between cadmium and lead exposure and blood pressure among workers of a smelting industry: a cross-sectional study

Abstract: BackgroundLead and cadmium are harmful heavy metals that are used for a variety of occupational purposes. Considering their potentially hazardous effects on health, studies on the association between exposure to these two heavy metals and health disorders have been actively conducted. This study aimed to determine the association between blood lead and cadmium levels and blood pressure in workers exposed to lead and cadmium in a smelter.MethodsNine hundred and sixty-three male workers who worked in a smelter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 47 publications
4
18
0
1
Order By: Relevance
“…Ind J Clin Biochem any significant change with age. This finding is in line with a study conducted by Chan et al [19] in which they reported increase in cadmium levels with age in individuals working in smelters. Poreba et al [20] assessed blood cadmium in workers of steel industry in Poland and reported significantly higher levels of CdB in exposed group(2.98 ± 3.29 lg/l) as compared to control group(1.41 ± 2.08 lg/l) which is similar to the findings in our study, where the mean blood cadmium levels of exposed individuals is 2.48 ± 1.20 lg/l.…”
Section: Discussionsupporting
confidence: 93%
“…Ind J Clin Biochem any significant change with age. This finding is in line with a study conducted by Chan et al [19] in which they reported increase in cadmium levels with age in individuals working in smelters. Poreba et al [20] assessed blood cadmium in workers of steel industry in Poland and reported significantly higher levels of CdB in exposed group(2.98 ± 3.29 lg/l) as compared to control group(1.41 ± 2.08 lg/l) which is similar to the findings in our study, where the mean blood cadmium levels of exposed individuals is 2.48 ± 1.20 lg/l.…”
Section: Discussionsupporting
confidence: 93%
“…No consistent differences in concentrations of metals were observed between hookah users and never tobacco users. Univariate analysis showed lower concentrations of cadmium in hookah users compared to never tobacco users, but this was likely confounded by the large difference in age between these two groups [ 39 ]. In fact, after adjusting for covariates, including age, there was no difference in cadmium levels between hookah users and never tobacco users ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The carcinogenic effect of other compounds is calculated in comparison to B(a)P. Personal monitoring of bus drivers (N = 50) in Czech Republic on 2 consecutive days showed statistically significant lower B(a)P and car-stolic blood pressure, was observed [34]. Tobacco smoking is another factor that increases exposure to heavy metals.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…The environmental and occupational exposure to lead and cadmium may be related to the development of hypertension, while lead has an additional documented neurotoxic and damaging kidneys effect [34,35]. Lead has been classified by IARC as an agent with a proved carcinogenic effect in animals, and as potentially carcinogenic to humans (Group 2A), whereas cadmium has been included in Group 1, i.e., among substances that are carcinogenic to humans.…”
Section: Heavy Metalsmentioning
confidence: 99%